Analysis of the Make Learning Fun Program on Kampus Mengajar Students’ in Classroom Management - Muharam, Suhari; Sobri, Ahmad Yusuf (Proceedings Series of Educational Studies, 2025)
The Make Learning Fun is a program for teaching campus students classroom management that focuses on creating an interesting and interactive learning environment for students. This approach aims to prevent boredom in the learning process so that students are expected to be more enthusiastic about participating in the learning process. This study examines classroom management strategies implemented by students who are members of the Teaching Campus program at SDN 4 Bedahan Depok. The researcher used a qualitative approach with a case study research design. The findings of this study show that the implementation of strategies in classroom management through the Make Learning Fun program was the first time created by teaching campus students at SDN Bedahan 4 Depok. Students are able to think innovatively in classroom management by making the learning process not only transfer knowledge but are able to create a fun, interesting, interactive learning atmosphere according to the needs of students without eliminating aspects of learning objectives. The findings of this study can be described as follows: (1) Student Approach to Classroom Management; (2) Kampus Mengajar Students’ Manage Classrooms Effectively; and (3) Students' Make Learning Fun Program in Classroom Management